ANALISIS PENERAPAN TRANSIT SIGNAL PRIORITY (TSP) PADA SISTEM TRANSJAKARTA BUSWAY Studi Kasus: Koridor VI (Ragunan – Kuningan) - Arief, Mohammad Ikhsan; Nahdalina, Nahdalina (Universitas Gunadarma, 2014)
Transjakarta Busway System is a BRT System deployed in DKI Jakarta. For more than 7 year operating, there’re still some obstacles in the system in which make the Busway system can’t operate effectively. In order to fix the system, for travel time aspect, there will be held a research in Simulation of Transit Signal Priority (TSP) in Transjakarta Busway System. The research will be held on the 6th Corridor (Ragunan – Kuningan). TSP is an intelligent transport system which modified the traffic light to better accommodate transit vehicle, so the travel time will be reduce but somehow the non-transit traffic is less disturbed. Simulation will be executed by VISSIM, a traffic simulator program. There will be three scenarios for TSP application: phase extension, red truncation, and phase advance. Based on VISSIM simulation, after TSP is deployed, the average travel time for Transjakarta Bus is 24.39 percent reduced for northbound travel (from Ragunan to Kuningan Timur) and 25.86 percent reduced for southbound travel (from Kuningan Timur to Ragunan) in peak period. For off peak period, the decrease is 26.44 percent for northbound travel and 34.92 percent for southbound travel. While the average side-street queue length increased by 2.10 percent and 1.20 percent for average cross-street queue length on peak period. And, the average side-street queue length on off peak period is increased by 28.87 percent. While the average cross-street queue length is increased by 1.67 percent.Keywords: Transit Signal Priority (TSP), Transjakarta Busway, VISSIM